Political Processes in Uzbekistan in the Context of the Problems of Political Tolerance (Global Journal of Human-Social Science, 2022)
Today, the political and philosophical category of "tolerance" is becoming more and more in demand in all areas of the socio-political life of Uzbekistan. The motive and term of tolerance organize discussions around themselves in the media, statements by human rights defenders, thoughts of educators, and calculations of social workers. However, against the backdrop of an increase in cultural and educational programs in the country to "introduce attitudes of tolerant consciousness", the covert activities of terrorist and extremist organizations are intensifying.
Keywords: political tolerance; political process; phenomenon; INGOs; democracy; law; political party; ideology